PERAN INOVASI PRODUK MEMEDIASI ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA PEMASARAN IMK SEKTOR INDUSTRI MAKANAN KOTA DENPASAR - Djayadiningrat, Adinda Fauziyyah; Sukaatmadja, I Putu Gde; Yasa, Ni Nyoman Kerti (E-Jurnal Manajemen, 2017)
This study was headed to ascertain the effect of entrepreneurship orientation towards the marketing performance which mediated by product innovation. Subject in this study was the owner of food small enterprise industries in Denpasar city, with 100 respondents as a samples. The analytical technique used by Path Analysis and Sobel Test. The results indicate that entrepreneurship orientation variables have a significant positive effect on product innovation and marketing performance. Product innovation variables also have a significant positive effect on marketing performance. Variable of product innovation also proven able to mediate entrepreneurship orientation to marketing performance on food small enteprise industries in Denpasar City. Implication of this study was emphasize the entrepreneurs to constantly add product variants, recognize risks and expand the reach of marketing areas to improve marketing performance.